2018
DOI: 10.1016/j.cbpc.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and functional variation within black snake venoms (Elapidae: Pseudechis )

Abstract: Pseudechis (black snakes) is an Australasian elapid snake genus that inhabits much of mainland Australia, with two representatives confined to Papua New Guinea. The present study is the first to analyse the venom of all 9 described Pseudechis species (plus one undescribed species) to investigate the evolution of venom composition and functional activity. Proteomic results demonstrated that the typical Pseudechis venom profile is dominated by phospholipase A toxins. Strong cytotoxicity was the dominant function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…In the Australian tigersnake clade (Notechis + Hoplocephalus + Paroplocephalus + Tropidechis), higher coagulotoxicity was associated with feeding on prey with higher metabolic rates [37], but metabolic rate of prey was scored only on a subjective 6-point scale rather than measured quantitatively, and no detectable effect of particular prey taxa was found. Although not formally tested, the pattern of coagulotoxicity in Pseudechis did not clearly match patterns of dietary variation across the genus [38], but the small sample size and low variation in coagulotoxicity in general prevented strong conclusions here. Each of these papers dealt only with a single type of functional activity (coagulotoxicity) and considered relationships with the extent of the activity in relatively small groups of closely related snakes, rather than comparing different activity types.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the Australian tigersnake clade (Notechis + Hoplocephalus + Paroplocephalus + Tropidechis), higher coagulotoxicity was associated with feeding on prey with higher metabolic rates [37], but metabolic rate of prey was scored only on a subjective 6-point scale rather than measured quantitatively, and no detectable effect of particular prey taxa was found. Although not formally tested, the pattern of coagulotoxicity in Pseudechis did not clearly match patterns of dietary variation across the genus [38], but the small sample size and low variation in coagulotoxicity in general prevented strong conclusions here. Each of these papers dealt only with a single type of functional activity (coagulotoxicity) and considered relationships with the extent of the activity in relatively small groups of closely related snakes, rather than comparing different activity types.…”
Section: Introductionmentioning
confidence: 82%
“…Current evidence to support (or oppose) these hypotheses is limited in geographic and phylogenetic scope, largely restricted to a set of studies on coagulotoxicity in clades within the single radiation of Australian elapid snakes [16,37,38]. Moreover, these studies have found variable support for Jackson et al's hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative that both academic and industrial bio-scientists are united in the search for some novel molecular solutions to this rapidly growing worldwide problem [32]. AMPs are now well-recognized to constitute a fundamental component of innate immunity and molecular defense in many living organisms, including bacteria [33,34,35,36]. AMPs demonstrated a certain characteristic to be potent and also broad spectrum in their action which can directly kill both Gram −ve and Gram +ve bacteria, including those strains which are resistant to traditional forms of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they have already been used many times to test hypotheses regarding animal venoms. For instance, pGLS has been used in several clades of Australian elapid snakes to investigate relationships between venom toxicity and diet [54,55], the cofactor dependence of toxic effects [54], the relationship between venom components and toxic effects [56], and the relationship between venom toxicology and antivenom efficacy [54]. As discussed in Section 1, drawing inferences about statistical relationships between traits such as coagulotoxicity and diet [54,55] is prone to being misleading when evolutionary history is ignored.…”
Section: Accounting For Phylogeny In Statistical Analysismentioning
confidence: 99%